On the Matter of Time. (June 2015) - Strang, Veronica
<x content-type="archive" xml:space="preserve">Abstract</x> Drawing on several disciplinary areas, this article considers diverse cultural concepts of time, space, and materiality. It explores historical shifts in ideas about time, observing that these have gone full circle, from visions in which time and space were conflated, through increasingly divergent linear understandings of the relationship between them, to their reunion in contemporary notions of space-time. Making use of long-term ethnographic research and explorations of the topic of Time at Durham University's Institute of Advanced Study (2012–13), the article considers Aboriginal Australian ideas about relationality and the movement of matter through space and time. It asks why these earliest explanations of the cosmos, though couched in a wholly different idiom, seem to have more in common with the theories proposed by contemporary physicists than with the ideas that dominated the period between the Holocene and the Anthropocene. The analysis suggests that such unexpected resonance between these oldest and newest ideas about time and space may spring from the fact that they share an intense observational focus on material events. Comparing these vastly different but intriguingly compatible worldviews meets interdisciplinary aims in providing a fresh perspective on both of them.